(untitled) (Arquivo Maaravi: Revista Digital de Estudos Judaicos da UFMG, 2007)
Sixty seven years to this month of November 2007, Aristides Sousa Mendes stood condemned to one year’s suspension on half pay followed by compulsory retirement from the diplomatic service. I will bring before you the case of this Portuguese diplomat, a Righteous Gentile, whom in the War’s darkest hour, faced with a political and social order contradictory to human dignity, submitted to moral obligation. Rather than seeking refuge in the magic of faith, he chose effective action, and used his power to help thousands of people escape the German westward advance, a decision for which he was himself to become an outcast – till his death and beyond, for it took almost 50 years for him to be reinstated.